Metal coating combining metal-ethylenediaminetetraacetic acid complex solutions and high-heat treatment via hydrogen/oxygen coupled flame - Keiji Komatsu; Takuya Kudo; Zhenyu Guo; Liang Shaoji; Atsushi Nakamura; Osamu Ito; Hidetoshi Saitoh (Results in Surfaces and Interfaces)
Direct metal Ni and Cu coatings were formed on various substrates using a metal-ethylenediaminetetraacetic acid (EDTA) complex solution followed by treatment with a high-heat hydrogen/oxygen (H2–O2) coupled flame. Mortar, alumina, and SUS304 were used to control the thermal histories of the samples. The formation of the metal phases was depended on the thermal history, especially the cooling rate after heat treatment. In addition, the oxidation of the formed metals was demonstrated by increasing the number of heat treatments. Hence, the obtained results indicated that metal coating by the combined application of metal-EDTA complex solutions and high-heat treatment via a hydrogen/oxygen coupled flame was accomplished.